STRUCTURAL SEGMENTATION OF SALT STRUCTURES IN THE FRONTAL RANGES OF THE KUQA FORELAND FOLD AND THRUST BELT, NORTHERN TARIM BASIN - Yu Y.; Tang L.; Jin W.; Wan G.; Yang W.; Peng G.; Lei G.; Ma Y. (My University, 2007)
Numerous salt structures have developed well in the Qiulitag structural belt which is located in the frontal ranges of the Kuqa foreland fold and thrust belt, northern Tarim Basin. Based on the field observation, well and seismic data, the types of salt structures can be divided into salt nappe, salt pillow, salt wall, salt wedding, fish-tail, salt-withdrawal minibasin, pop-up, fault propagation fold, fault bend fold and triangle zone. The geometric and kinematic features of salt structures vary along the strike of the belt, and structural segmentation is very obvious. The structural segmentation of salt structures is mainly referred to their perpendicular assemblages where there are paleo-uplift (subsalt)-salt pillow (salt layer)-thrust (overburden) in the Quele region, structural slope (subsalt)-salt wall (salt layer)-fault propagation fold, inversion anticline and syncline (overburden) in the Xiqiu region, and fault bend fold (subsalt) - salt nappe (salt layer)-fault propagation fold (overburden) in the Dongqiu region. The major factors influencing the segmentation of salt structures include the diversities of basement faults, salt layers, transfer zones and deformation space, of which the basement tectonics and salt layers had imposed the most important effects on the segmentation of salt structures.
Keywords: FAULT-RELATED FOLD; KUQA FORELAND FOLD AND THRUST BELT; SALT TECTONICS; STRUCTURAL SEGMENTATION